Сучасний стан видів роду калина (Viburnum L.) в умовах колекційних і паркових насаджень Києва - Demchenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The history of introduction and present state of guelder rose (Viburnum L.) species under conditions of Kyiv city collectional and parks plantations have been stated. Eleven species and four forms of guelder rose have been found.